Determination of maximum pvc reclaimed material content in pvc soles compound, observed from tehno economics point of view - Susilowati Susilowati et. al. (Majalah Kulit, Karet, dan Plastik, 1988)
The objectives of the study is to obtain a formula of soles compound, by determining the content of maximum PVC reclaimed material added into the batch, observed from the view point of economic study, which means to obtain a soles compound formula, the physical properties of which meet the SII 1103 – 84 Sol Lentur Cetak PVC (moulded flexible PVC soles), which produces low price soles.          The research is emphasized on variation of volume of  PVC reclaimed  material added into the batch, based on SII 1103 -84. The result of this research shows that composition of different compound produces different melting point as well.          Where as the volume of maximum PVC reclaimed material added into the batch is 40%, and it is found from economic study that soles compound which contains 40 % PVC reclaimed material and 60 % non PVC reclaimed material ( consist of PVC 100% , SOP 60%, epoxy 6%, Ba Cd Zn 2%, CaCO3 10 % Carbon black 0,05%). Produces the best soles that is good physical properties and cheap price ( Rp. 552,85/pair).